Anti-cancer effect of bee venom on colon cancer cell growth by activation of death receptors and inhibition of nuclear factor kappa B - Zheng, Jie (Oncotarget, 2015)
Bee venom (BV) has been used as a traditional medicine to treat arthritis, rheumatism, back pain, cancerous tumors, and skin diseases. However, the effects of BV on the colon cancer and their action mechanisms have not been reported yet. We used cell viability assay and soft agar colony formation assay for testing cell viability, electro mobility shift assay for detecting DNA binding activity of nuclear factor kappa B (NF-κB) and Western blotting assay for detection of apoptosis regulatory proteins. We found that BV inhibited growth of colon cancer cells through induction of apoptosis. We also found that the expression of death receptor (DR) 4, DR5, p53, p21, Bax, cleaved caspase-3, cleaved caspase-8, and cleaved caspase-9 was increased by BV treatment in a dose dependent manner (0–5 μg/ml). Consistent with cancer cell growth inhibition, the DNA binding activity of nuclear factor kappa B (NF-κB) was also inhibited by BV treatment. Besides, we found that BV blocked NF-κB activation by directly binding to NF-κB p50 subunit. Moreover, combination treatment with BV and p50 siRNA or NF-κB inhibitor augmented BV-induced cell growth inhibition. However, p50 mutant plasmid (C62S) transfection partially abolished BV-induced cell growth inhibiton. In addition, BV significantly suppressed tumor growth in vivo. Therefore, these results suggested that BV could inhibit colon cancer cell growth, and these anti-proliferative effects may be related to the induction of apoptosis by activation of DR4 and DR5 and inhibition of NF-κB.